THE USE OF THE JAVANESE GAMELAN AS MEDIUM OF CULTURAL HERITAGE AT GKJ GONDOKUSUMAN YOGYAKARTA - Krisno Utomo, Yunatan; Sumaryono, Totok; Rohendi Rohidi, Tjetjep; Ganap, Victor (International Journal of Psychosocial Rehabilitation, 2024)
The background to the study of the use of Javanese gamelan as a cultural heritage medium in Javanese Christian Church (GKJ) Gondokusuman is the church’s awareness of the importance of cultural conservation for religious people who live in a socio-cultural environment.The purpose of this study is to analyze the use of Javanese gamelan as an inheritance of Javanese cultural values in GKJ Gondokusuman congregation. This study used a qualitative method with a phenomenological research design with an interdisciplinary study approach. This study found that the use of Javanese gamelan in congregational worship can be a medium for educational inheritance, both spiritual and cultural education. In addition, the practice of gamelan in worship is able to increase appreciation and encouraging the practice of religious life.The application of art and culture in the context of worship can be a dynamic force in realizing the education of Javanese people who are both religious and also cultured.